The dual nature of blazar fast variability: space and ground observations of S5 0716+714 - Raiteri, Claudia Maria; Kurtanidze, Sofia O.; Kurtanidze, Omar M.; Nikolashvili, Maria G. (Monthly notices of the Royal Astronomical Society, 2021)
Blazar S5 0716+714 is well-known for its short-term variability, down to intraday time-scales. We here present the 2-min cadence optical light curve obtained by the TESS space telescope in 2019 December-2020 January and analyse the object fast variability with unprecedented sampling. Supporting observations by the Whole Earth Blazar Telescope Collaboration in B, V, R, and I bands allow us to investigate the spectral variability during the TESS pointing. The spectral analysis is further extended in frequency to the UV and X-ray bands with data from the Neil Gehrels Swift Observatory. We develop a new method to unveil the shortest optical variability time-scales. This is based on progressive de-trending of the TESS light curve by means of cubic spline interpolations through the binned fluxes, with decreasing time bins. The de-trended light curves are then analysed with classical tools for time-series analysis (periodogram, autocorrelation, and structure functions). The results show that below 3 d there are significant characteristic variability time-scales of about 1.7, 0.5, and 0.2 d. Variability on time-scales $\lesssim 0.2$ d is strongly chromatic and must be ascribed to intrinsic energetic processes involving emitting regions, likely jet substructures, with dimension less than about 10−3 pc. In contrast, flux changes on time-scales $\gtrsim 0.5$ d are quasi-achromatic and are probably due to Doppler factor changes of geometric origin.
Published: 17 November 2020
Gesehen am 10.03.2021